Palladium‐Catalyzed Direct Cross‐Coupling of Carboranyllithium with (Hetero)Aryl Halides. Issue 49 (26th October 2016) - Lu, Ju‐You; Wan, Hong; Zhang, Jianwei; Wang, Zhixuan; Li, Yang; Du, Yongmei; Li, Chunying; Liu, Zhao‐Tie; Liu, Zhong‐Wen; Lu, Jian
Abstract: A palladium‐catalyzed direct C‐arylation reaction of readily available cage carboranyllithium reagents with aryl halides has been developed for the first time. This method is applicable to a wide range of aryl halide substrates including aryl iodides, aryl bromides, and heteroaromatic halides. Abstract : Palladium‐catalyzed direct C‐arylation of readily available cage carboranyllithium reagents with aryl halides has been developed for the first time. This method is applicable to a wide range of aryl halide substrates including aryl iodides, aryl bromides, and heteroaromatic halides.